2022
DOI: 10.3389/fpsyg.2022.992310
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress and growth in adolescent childhood cancer survivors: Links to quality of life

Abstract: Pediatric cancer can be considered an event potentially leading to posttraumatic stress symptoms (PTSS) as well as posttraumatic growth (PTG). While clinically significant levels of PTSS are rare in childhood cancer survivors, PTG is common in this population. However, the relationship of PTG to overall adaptation and quality of life (QOL) in pediatric cancer patients is not clear. Therefore, our study aims to analyse the relationships of PTSS and PTG with QOL in childhood cancer survivors. In this study, 172 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
0
2
0
5
Order By: Relevance
“…Los estudios que abordan la prevalencia (12,19,21) , coinciden en afirmar que aparece en supervivientes tiempo después del diagnóstico. Sin embargo, no ocurre en proporciones muy altas.…”
Section: Resultados Sobre Estrés Postraumático (Ept); (Objetivo Espec...unclassified
See 2 more Smart Citations
“…Los estudios que abordan la prevalencia (12,19,21) , coinciden en afirmar que aparece en supervivientes tiempo después del diagnóstico. Sin embargo, no ocurre en proporciones muy altas.…”
Section: Resultados Sobre Estrés Postraumático (Ept); (Objetivo Espec...unclassified
“…En la investigación de Okado et al (19) , con una muestra de 209 participantes, se observan síntomas de EPT en, aproximadamente, el 30%. Por último, en el trabajo de Koutná et al (12) , con una muestra de 125 participantes, el porcentaje de EPT es mucho menor, en torno al 0,55%. De acuerdo con este último, los factores de riesgo para una mala adaptación y desarrollo de EPT a raíz del cáncer son: ser mujer, tener antecedentes familiares de problemas psicológicos y haber padecido un tumor en el SNC.…”
Section: Resultados Sobre Estrés Postraumático (Ept); (Objetivo Espec...unclassified
See 1 more Smart Citation
“…Some studies suggested that quality of life was positively correlated with PTG, indicating that quality of life can be improved by developing PTG [ 52 , 53 ]. Nevertheless, a few studies have found null or negative relations between them [ 54 , 55 ]. The reasons for these differences may be related to the following factors: i) different traumatic events may have different effects on PTG and quality of life, ii) some unidentified potential variables may change the relationship between PTG and quality of life, and iii) differences in sampling methods and research design methods between different studies lead to the inability to directly compare the results of various studies.…”
Section: Discussionmentioning
confidence: 99%
“…It evokes a sense of threat to a person's sense of vulnerability, or a loss of control, a sense of helplessness (Mercadante et al, 2004;Carlsson et al, 2019). Growing body of research indicates that posttraumatic stress disorder (PTSD) and symptoms (PTSS) are some of the most important psychological consequences for those affected by childhood cancer (Portigliatti Pomeri et al, 2021), as well as their parents and siblings (Tremolada et al, 2016;Koutná et al, 2022). The traumatic experience of cancer illness usually starts at diagnosis communication, continuing throughout the course of care until the end of treatment and beginning of the survivorship phase .…”
Section: Introductionmentioning
confidence: 99%